Multicenter prospective study for clinical and endoscopic efficacies of leukocytapheresis therapy in patients with ulcerative colitis. (April 2013) - Okuyama, Yusuke; Andoh, Akira; Nishishita, Masakazu; Fukunaga, Ken; Kamikozuru, Koji; Yokoyama, Yoko; Ueno, Yoshitaka; Tanaka, Shinji; Kuge, Hiroyuki; Yoshikawa, Syusaku; Sugahara, Atsushi; Anami, Emi; et al.
Abstract Objective. This study aimed to assess the efficacy and tolerability of leukocytapheresis (LCAP) and to investigate predictive factors for mucosal healing and a sustained clinical response in steroid-free and steroid-refractory patients with ulcerative colitis (UC). Material and methods. Thirty-one steroid-free or steroid-refractory patients with active UC were enrolled. Five or ten consecutive sessions of LCAP were performed in each patient. The efficacy and tolerability was then evaluated at weeks 3 and 6. Endoscopic examination was performed at week 6 to evaluate the mucosal healing, and the sustained cumulative response rate was evaluated at 12 months. Results. At week 6, the mean Mayo clinical activity score had decreased significantly from 8.0 to 4.6 in the steroid-free patients and from 8.3 to 3.9 in the steroid-refractory patients. Rachmilewitz's endoscopic index had also decreased significantly from 9.1 to 6.1 in the steroid-free patients and from 10.0 to 5.7 in the steroid-refractory patients. Forty-seven percent of the steroid-free patients and 33% of the steroid-refractory patients achieved mucosal healing. The peripheral platelet counts had decreased significantly at weeks 3 and 6 in the mucosal healing group, compared with the non-mucosal healing group. The patients with a more than 15% platelet reduction had a significantly higher cumulative response rate, compared with the patients without a platelet reduction (p = 0.015). Conclusions. LCAP is beneficial for the induction of mucosal healing in steroid-free and steroid-refractory patients with UC. The degree of platelet reduction during LCAP might be a predictive marker for mucosal healing and a sustained clinical response.